THE EFFORT TO IMPROVE LEARNING ACTIVENESS USING A FIRING LINE STRATEGY IN MATHEMATICS LESSON ON THE STUDENTS OF GRADE XI - Sintiya Wahyu Lestari; Abdul Taram (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Observation on the students of grade XI MIPA 2 at State Senior High School (SMA Negeri) 3 Bantul showed that students' learning activeness to participate in mathematics lesson was still lacking. Therefore, this study aims to improve learning activeness using a firing line strategy in mathematics lessons on grade XI MIPA 2 at SMA Negeri 3 Bantul in 2017/2018. This research is classroom action research. The action is carried out in three cycles. In this study, subjects were 31 students' of grade XI MIPA 2, 9 men and 22 women. Objects in this study were the learning activities that applied the active strategy of the firing line. Methods of data collection were the method of observation, questionnaires, interviews, and documentation. Data analysis was descriptive qualitative, and quantitative. The results showed that learning using the firing line strategy to improve students' learning activeness in each cycle has improved. The questionnaires of the learning activeness in cycle I was 53.59% (low), it increased in cycle II by 66.89% (high), and in the third cycle was 72,38% (high). The results of student observations were in the first cycle of 69,95%, it increased in the second cycle of 83.29%, and 86.90% for the third cycle. This research's success is also characterized by an average quiz that has reached the MCC (>69). The results of the quiz in cycle II were 78,33 and in the third cycle was 76,67.